2001
DOI: 10.1023/a:1009522917352
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The zinc(II)-binding affinities of recombinant human growth hormone and two its mutants, 14-33 and 14-95, were studied using Immobilized Metal Ion Affinity Gel-electrophoresis (IMAG). The mutant hormones, composed of polypeptide chain segments of the human and porcine growth hormones, lacked His18, which may be crucial for binding of the intact hormone to the transition metal ions. The mutations did not affect the affinity of human growth hormone to immobilized zinc ions; the structural analysis implied that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Expression plasmids for GHs were constructed by replacement of gene 10 in pGEMEX1 (Promega) with a GH gene [2]. Proteins were purified from the Escherichia coli strain BL21(DE3) harboring the corresponding expression plasmid [7].…”
Section: Methodsmentioning
confidence: 99%
“…Expression plasmids for GHs were constructed by replacement of gene 10 in pGEMEX1 (Promega) with a GH gene [2]. Proteins were purified from the Escherichia coli strain BL21(DE3) harboring the corresponding expression plasmid [7].…”
Section: Methodsmentioning
confidence: 99%
“…IMAGE technique was also applied to study the change of the surface histidines topography of RNase A when chemically glycosylated on exposed carboxylic groups with glucosamine using carbodiimide as cross-linker, under mild conditions [65]. The Zn(II) binding region in growth hormone was studied using IMAGE by Anisimove et al [66]. Using IMAGE structural study of natural and chemically induced oligomeric ribonucleases was done to study the relationship between surface histidine topography in oligomeric forms of these ribonucleases and their catalytic properties [67].…”
Section: Immobilized Metal-ion Affinity Gel Electrophoresismentioning
confidence: 99%
“…This in turn can give information about the structural differences resulting in different functional properties. Structural study and the structure-function relationship of natural and chemical induced oligomeric ribonuclease were also studied using IMACE [66]. Effects of chemical glycosylation with glucosamine of bovine α-chymotrypsin on its catalytic and structural properties, particularly their modification of the affinity for the transition-metal chelate, IDA-Cu(II) was studied by Jiang et al [70] using IMACE.…”
Section: Immobilized Metal-ion Affinity Capillary Electrophoresismentioning
confidence: 99%
“…The variable X residue was positioned in the middle of the peptide to best represent the characteristics of a midchain amino acid in a protein by positioning it relatively far from the zwitterionic end groups. In this initial set of adsorption studies, three different types of amino acids were used for the X residue to vary the overall characteristics of the peptides, with X represented by either threonine (T; -CH(CH 3 )OH side chain, polar character), aspartic acid (D; -CH 2 COOH side chain, negatively charged, p K = 3.9 ), or valine (V; -CH(CH 3 ) 2 side chain, nonpolar character). Each of these three peptides was synthesized and characterized by analytical HPLC and mass spectral analysis by SynBioSci Corporation (Livermore, CA), which showed that all of the peptides were ≥98% pure.…”
Section: Introductionmentioning
confidence: 99%